CONCEPT OF STRUCTURAL ORGANIZATION INFORMATION SITUATIONAL CENTERS FOR OPERATIONAL MANAGEMENT MACHINEBUILDING DIVISION WITH A GEOGRAPHICALLY DISTRIBUTED PRODUCTION - Alexander V. Rechkalov; Alexander V. Artukhov; Konstantin A. Rizvanov (Статистика и экономика)
The article considers the problem of organizing the planning system based on virtual manufacturing in constructingsituational center for engineering division. The analysis of foreign and domestic experience in the ﬁeld of situational management, organization planning and managementsystems as virtual production in relation to the real (underlying) production is provided. The scheme of organization situational center for engine-building enterprises of theEngineering Division is given.